Concerns about the microbiological quality of traditional raw milk cheeses: a worldwide issue (International Journal of Health, Animal Science and Food Safety, 2014)
Six types of unripened raw milk fresh (Robiola, Crescenza, Primo sale and Formaggella) and  “pasta filata” cheeses (Mozzarella and Burrata) were evaluated for microbiological parameters. No Listeria monocytogenes or Salmonella spp. were detected, but high microbial counts were revealed. Significantly higher Total Viable Counts (TVC) and Enterobacteriaceae counts were observed in “fresh cheese” than in “pasta filata” samples. Values > 6 Log CFU/g were found in 81.3% of fresh vs 50% in pasta filata for TVC and 65.6% vs 12.5% for Enterobacteriaceae, respectively. An evident contamination by Escherichia coli, Coagulase-positive Staphylococci and Pseudomonas spp. was detected in all the cheeses: the causes could be the improper hygiene of the artisanal production practices and the permanence of the cheeses on the refrigerated shelves. A careful attention to the respect of the good manufacturing practices is suggested to avoid the presence of initial high bacterial loads.
Keywords: fresh cheeses; microbiological quality; unpasteurized milk; food safety.